Las lecturas de Hidacio de Chaves. Notas sobre la recepción literaria en la Gallaecia del s. V (Minerva. Revista de Filología Clásica, 2019)
By closely analysing the Chronicle of Hydatius of Chaves, I have tried to find out to what extent and until when literary works of that time still reached the Gallaecia. Some authors and their works have been mentioned by Hydatius within the biographic notes of the Chronicle, e. g. Augustinus, Sulpicius Severus, and Hieronymus. Besides these, one can detect some language parallels to works that have not been openly mentioned by Hydatius, e. g. possibly the Vulgata. The result of this investigation, is that the reception of literary works in the Gallaecia until 415 to 420 A. D. was still possible without much delay, whereas after those years Hydatius only has noted reception of letters.